Integração de tecnologias educacionais em rede pelos estudantes-estagiários do curso de formação de professores para a educação profissional: portais e recursos educacionais digitais - Aguiar, Deliane Costa de (2019)
This research was carried out in the Masters in Education, in the research line School Practices and Public Policies. It addresses the use of Educational Portals and Digital Resources by PEG trainees in Vocational Education. How these tools are used in school practices in vocational and technological education by trainees. The focus will be on open educational resources (OERs) and educational portals as the teacher portal, and how interacting with these resources provides the building of knowledge. Among the resources are hypertexts, videos, simulations, animations. Search for different educational resources. The specific objectives are: Check which digital resources PEG students use in oriented teaching. Justify the importance of the use of varied digital resources and the teacher's portal in teaching. To report experiences of PEG students in stage III, how they used the resources in their classroom practices, their challenges and possibilities. The methodological perspective will be the "Research-Action" defined by the authors Elliott (1978), Kemmis and Mctaggart (1992), Carr and Kemmis (1988), It will also be documentary through the student training dossiers of PEG. The field research will be with PEG stage III students. The research was conducted in three cycles. In the first cycle, we performed an initial diagnosis through documentary analysis of the ESE III reports from 2016 to 2018. At this stage we concluded that the REDs most used by Student Interns were videos taken from Youtube and google images, and only one used resource public portal, a simulation of the MEC Teacher Portal. In the second cycle, through participant observation with ESE II Student Interns in the second half of 2018, we examined the didactic sequences (planning sets) to see what resources they chose to mediate their practices in ESE III in the subsequent semester. As a result the most cited resources were videos, images from Youtube and google and one student cited activity with smartphone. In the third cycle we conducted an educational intervention in an ESE III class, in order to encourage the use of digital resources from public portals. The educational intervention was through a class on the main Educational Portals and the students chose at least one resource to mediate one of their classes, as well as monitoring the weekly plans of the classes they gave. Still in this third cycle, we implemented a questionnaire with all student-students enrolled in ESE III in the semester (first semester of 2019), using the ProfTest platform, with the purpose of mapping the other digital resources used by the trainees and, also, the reasons for the some did not integrate such technologies into teaching.As conclusions we highlight: that student-interns prefer to look for digital educational resources to mediate their educational practices on youtube and google. The data reveal that student-trainees are integrating TER into their educational practices through videos and images, some of which are also using mobile activities. Among the challenges pointed out by student interns regarding the use of Digital Educational Resources in their Practices, we point out that cell phones are still prohibited by schools from being used in class; find varied and updated materials; learn and teach when the teacher-teacher uses an application or program; Correctly choose the best and most appropriate features and social problems the student does not own a mobile device. We highlight as possibilities mentioned by the student-interns that the REDs draw students' attention, help to combine theory and practice, complement the teacher's explanations and mobilize the student's interest in the content addressed.